Demand for Feng Shui Stones in Vietnam: Cultural Belief and Consumer Behavior (International Journal of Scientific Research and Management (IJSRM), 2025)
This study investigates the demand for Feng Shui stones in Vietnam through the lens of cultural belief and consumer behavior, drawing on data from a survey of 149 respondents. Feng Shui, deeply embedded in Vietnamese cultural and spiritual life, influences a wide range of consumer decisions. The research examines how beliefs in energy balance, luck, and prosperity contribute to the popularity of Feng Shui stones, and identifies key demographic and psychographic factors driving their purchase. Results from the survey indicate that consumers are motivated not only by aesthetic and decorative appeal but also by spiritual significance and perceived metaphysical benefits. The study underscores the importance of cultural traditions in shaping contemporary consumer behavior and offers insights for businesses seeking to align products with culturally embedded values.